STRATEGI GURU MENDISIPLINKAN SISWA DALAM PROSES BELAJAR MENGAJAR - Tamjidillah Hm Amin (FASHLUNA, 2021)
The purpose of this study is to find out how the teacher's strategy is to discipline students in the teaching and learning process in schools. This research is a qualitative research with a descriptive approach, the data collection methods used are observation, interviews and documentation. This research is a qualitative research. Sources of data in this study were principals, teachers, staff, and students. The data collection method used is the method of interview, observation and documentation. The data analysis technique uses data reduction, data presentation, and verification of observations, increasing persistence and triangulation. The result of this research is to show how the teacher's strategy is to discipline students in the teaching and learning process. In addition, another teacher strategy is to approach students personally and in groups related to the cultivation of a spirit of self-discipline, both discipline towards healthy and clean living habits, discipline in self-regulation and the environment, social order, living together in cooperation and mutual cooperation and etc.